Cyclic response of laminated bamboo lumber nailed connection: Theoretical modelling and experimental investigations. (January 2022) - Chen, Guo; Wu, Xintao; Jiang, Hao; Wang, Zhenguo; Yin, Mingyang
Abstract: The interest in the use of laminated bamboo lumber (LBL) as a new green building material is growing rapidly, but little work has been conducted on the cyclic response of LBL nailed connection, which consists of LBL middle member sandwiched between two LBL plates. Experiments on 90 LBL-to-LBL nailed connections are done to study the effect of nail diameter and loading direction to the grain on cyclic behavior of the connections. It is found that the failure mode of the connections loaded monotonically is due to the formation of two hinges of nail, which is quite different from the connections loaded cyclically. Two plastic hinges are also observed in nails during the cyclic tests, in addition, most of the nails in connections fail in low cycle fatigue fracture due to reversed bending of nails. The load-carrying capacity, stiffness, and energy-dissipating capacity of the connections can be significantly improved by using larger-diameter nails as connectors, while decreases slightly with the increase of loading direction to grain. Regarding to the displacement ductility ratio, whether monotonic loading or cyclic loading, the connections show low ductility performance. The equivalent viscous damping coefficient decreases with the increase of the nail diameter, and not relates with the loading direction to the grain. The load-slip response of the LBL nailed joints exhibits pinched hysteretic behavior with strength and stiffness degradation under cyclic loading. The modified Dolan theoretical model can be used to predict the cyclic response of the LBL nailed connections.